Genetic and cytogenetic analysis of the Adh region in Drosophila melanogaster. - O'Donnell, J.M.; Mandel, H.C.; Krauss, M.; Sofer, W. (Genetics, 1977)
Eighteen Adh-negative mutations were selected with 1-pentyn-3-ol after feeding of formaldehyde. Twelve of the 18 were shown by cytological and genetic analysis to be deletions. Cytological examination of the deletions allowed us to localize the Adh gene to a region including bands 35B3-5 on the left arm of chromosome 2. The deletions were also used to order known visible loci located near Adh.--The vital loci near Adh were also investigated. A total of 109 lethal mutations were generated with EMS and 33 of these, localized within a region defined by the overlap of two of the deletions, were found to belong to 13 complementation groups. If one includes three other loci known to belong there (el, Adh and Sco) a total of 16 complemetation groups have been identified in the region close to Adh.